Layer- and cell type-selective co-transmission by a basal forebrain cholinergic projection to the olfactory bulb - Daniel T. Case (Nature Portfolio, 2017)
Cholinergic neurons innervate multiple layers in the main olfactory bulb but the precise circuitry of this input is not known. Here the authors show that VGLUT3+ cholinergic neurons selectively innervate deep short axon cells in specific layers and elicit robust monosynaptic GABAergic and nicotinic postsynaptic currents.